Los Modelos de Depreciación Aplicados en la Valuación de Bienes Inmuebles - Artavia-Jiménez, Diengo Andrés (Instituto Tecnológico de Costa Rica, 2012)
The theme of the project below is for “depreciation models applied in the real estate valuation.” This project was designed with the objective of investigating the methodologies used to estimate the depreciation of real estate throughout Latin America, determining which is more effective and suitable for the real estate market in Costa Rica. For the analysis of the research topic, there are different theoretical and actual developed examples, where different methods were applied to find the value of depreciation. Results were compared to determine which method is the most efficient and attached to the reality of the estate. Finally, surveys were applied to different specialists to know their points of view about the subject. With this, we were able to understand exactly each one of the methodologies. Also, we obtained positive and negative aspects of each general method, mainly the method of Ross Heidecke. In conclusion, we obtained important recommendations, which will be used by professionals in the future to create a more efficient model, which can be applicable in Costa Rica.
Proyecto de Graduación (Licenciatura Ingeniería en Construcción) Instituto Tecnológico de Costa Rica. Escuela Ingeniería en Construcción, 2012.
Keywords: Ross Heidecke; Inmobiliaria; Depreciación; Maquinaria; Edificación